Pengaruh Penggunaan Media Kartu Bergambar Terhadap Peningkatan Pengetahuan Kesehatan Gigi dan Mulut Pada Siswa Kelas V SD Negeri 212 Harapan Kota Bandung - Arifin, Naufal Aqila; Chaerudin, Denden Ridwan; Utami, Ulfah (Poltekkes Kemenkes Bandung, 2024)
Increasing dental health knowledge is very important from an early age because it will have an impact on the health of the teeth and mouth. The way to increase knowledge is by learning. Learning can be done using effective media. The aim of this research is to find out how the use of picture card media influences students' increased understanding of dental and oral health. Pre-experimental research using a single group design before and after the test is the type of research that is needed. Sampling was carried out using total sampling technique. The sample in this study amounted to 53 students. The variables in the research were picture card media and student knowledge. The picture card media has been tested and deemed appropriate by media and materials experts. Hypothesis testing uses the Wilcoxon test. The average score for oral health knowledge before the intervention was 70.96 and after the intervention it increased to 96.12. Wilcoxon Sign Rank Test analysis shows p-value (0.000)